Detection and Classification of Single Machining Error of Non-circular Gear - Dai Jianqing; Wang Shengze (Jixie chuandong)
The studies on non-circular gear cutting and using errors are generally based on theory of cylindrical gear errors,and the similarities and differences between cylindrical gear and non-circular gear are combined to study the change rule of non-circular gear contacting line and obtained corresponding conclusions.From a different perspective,by starting from the non-circular gear engagement principle,on the basis of analyzing the concrete geometric error conditions,the new type tooth profile algorithm routine is reasonably modified,and the non-circular gear tooth profile error contrast figure is obtained.Furthermore,the theoretical verification is carried out by incorporating analytical method and contacting line incremental method,a reasonable classification method is proposed based on the characterization of the error characteristic code in the general case and the error genetic map used to guide practical production is summed up which possess enormous significance to non-circular gear machining.